O discurso do poder-saber em Michel Foucault: reflexão sobre a sexualidade na Igreja Cristã e aconselhamento pastoral - Nunes, Jone (2014)
This thesis analyzes the discourse in the relations between power-knowledge in sexuality present in the religious institutions, especially in Christian churches, having as a theoretical reference the work of the French philosopher Michel Foucault. Understanding the religious discourse about sexuality based on Foucault is to admit that the religious discourse is an object of power present in the historicity of the power devices which act on the body-sex of each individual-human, as well as in the existence of pleasure, its unique, singular, particular way of life. One will also examine the way in which sexuality was used as a power device throughout history and how it is embodied in current times. One perceives few changes since the implantation of Protestantism in Brazil, due to the strength with which the power and the knowledge were established within the discourse elaborated by the religious leaderships, which based themselves on a distorted interpretation of the Holy Scriptures. The culture of each group needs to be analyzed as a reference to obtain a better comprehension of the acts and behaviors of a certain social group and not take it as a model. With regard to sexuality, one needs to understand why it is the object which most perturbs the religious institutions and is used as something to bind the individual to sin. Where are the concepts of sin? How can one understand them, when one perceives that, in between lines, many Christian churches, when preserving life , prohibit life, underestimating sexuality? There is not just one reason or one truth which can be used to establish an authentic relation. The tradition or subjection is nothing more than fact situations. What persists is that the church is made up of subjects, subject-individuals .